Educational Experiences of Educational Administration Master Students - Hüseyin Serin; Hatice Ergin-Kocatürk (Anı Publishing, 2019)
Educational Administration graduate programs are among the programs that students frequently apply at state and foundation universities. The main purpose of the programs, which are generally preferred by undergraduates of the Faculties of Education, is to train the required education administrators. Being a graduate of Educational Administration programs have little contribution to be appointed as an educational administrator at state schools. This situation arouses interest in the aims, expectations and achievements of the students who direct to the field of Education Administration in order to receive graduate education. The aim of this study is to make a general evaluation and make a variety of suggestions for the field of Educational Administration and its programs by examining aims and gains of graduate students attending the Educational Administration graduate programs at the state and foundation universities. The study was designed with a phenomenological approach and included 21 students, 12 from state universities and 9 from foundation universities. The data collected by the semi-structured interview form were analyzed by content analysis. Generally, participants stated that they started graduate education for personal and professional purposes. Various differences were observed among the participants from state and foundation universities. The most obvious one among those differences is aims of participants while choosing this field. Findings of the study emphasize necessary formations on training and recruitment of educational administrators.